DEATH AND REINCARNATION AS INSPIRATION OF CREATION FINE ARTWORK - Kariana, I Nengah; Wirakesuma, I Nengah; Ruta, I Made (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2025)
This report contains a description of the creation of works of art that take the theme "Death and Reincarnation as Ideas in the Creation of Works of Art" which was inspired when reading a book that made the author interested in raising the theme of death in this semester IV independent project, namely the book "History of Death" from Michael Kerrigan. It reminded the author of the confusion of finding a concept and finally it was recommended to use a concept that was close, so the author raised death because there is nothing closer to death. The goal to be achieved in the creation of this work is to find out how death and reincarnation are packaged in religious sciences, cultures that exist in Indonesia, especially Bali through creativity and imagination into the form of paintings using various techniques, media, considering the elements and principles of fine art. From the written work and paintings produced, the author hopes that this work will be useful as literacy and a source of inspiration for society in the future. From the above theme, there are 5 (five) works that can be realized from death and reincarnation that can provide an overview of culture and religious science about death and reincarnation, especially in Bali.